1989
DOI: 10.1016/s0006-3495(89)82735-3
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in the assembly of polyomavirus capsid protein VP1

Abstract: Polyomavirus major capsid protein VP1, purified after expression of the recombinant gene in Escherichia coli, forms stable pentamers in low-ionic strength, neutral, or alkaline solutions. Electron microscopy showed that the pentamers, which correspond to viral capsomeres, can be self-assembled into a variety of polymorphic aggregates by lowering the pH, adding calcium, or raising the ionic strength. Some of the aggregates resembled the 500-A-diameter virus capsid, whereas other considerably larger or smaller c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
217
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(237 citation statements)
references
References 33 publications
18
217
2
Order By: Relevance
“…The pleomorphic nature of the interactions between the dimers of dimers that modulate the size of the final mHBsAg particle presumably underlie also the switch to icosahedral assembly that is required to form the complete HBV particles. This mechanism appears to be an extension of the conformational switching mechanism recognized as the cornerstone to the assembly of many icosahedral virus particles (15,(30)(31)(32). Finally, the antigenic properties of these particles, many millions of doses of which are administered every year as a recombinant HB vaccine, confirm that the presentation of surface epitopes on the octahedral structures mimics that in the intact virus.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…The pleomorphic nature of the interactions between the dimers of dimers that modulate the size of the final mHBsAg particle presumably underlie also the switch to icosahedral assembly that is required to form the complete HBV particles. This mechanism appears to be an extension of the conformational switching mechanism recognized as the cornerstone to the assembly of many icosahedral virus particles (15,(30)(31)(32). Finally, the antigenic properties of these particles, many millions of doses of which are administered every year as a recombinant HB vaccine, confirm that the presentation of surface epitopes on the octahedral structures mimics that in the intact virus.…”
Section: Resultsmentioning
confidence: 69%
“…Polyomavirus shows a level of pleomorphism similar to that of HBV: both form tubular structures as well as octahedral and icosahedral assemblies (33). Polyomavirus VP1 is able to assemble into these different structures as a result of changes in the way the pentamers link together, rather than changes in the basic building block of the assemblies (32,33). The SHBsAg dimers seem to echo this principle.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been demonstrated that bacterially expressed recombinant VP1 can self-assemble into capsid-like particles in vitro in the presence of calcium ions (Haynes et al, 1993 ;Salunke et al, 1986Salunke et al, , 1989 and that eukaryotic baculovirus-expressed polyomavirus VP1 can also produce capsid-like particles in the nuclei of insect cells (Delos et al, 1993 ;Forstova! et al, 1993 ;Li et al, 1995 ;Montross et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Namba et al (1988) described a related method to enhance displays of macromolecules, in which a smooth gradient of color is added to provide radialdepth cueing (R cueing) from the center of quasispherical structures (e.g., icosahedral viruses) or from the central axis of quasi-cylindrical structures (e.g., helical filaments). Salunke et al (1989) used this same style of R cueing in a computer-created model for polyomavirus virions. More recently, Grant et al (1992) used radial color gradients to highlight topographical features on the surfaces of small icosahedral viruses analyzed by X-ray crystallography.…”
Section: Introductionmentioning
confidence: 99%